Evaluation for additional work of shoring pile work in zone B - BUCG-ABC Joint Venture (BUCG-ABC JV) (Brac University, 2023)
This record consists of general correspondence regarding the evaluation for additional work of shoring pile work in zone B of BRACU new campus project site